Pengaruh Manajemen Laba terhadap Nilai Perusahaan dengan Variabel Pemoderasi Pengungkapan Tata Kelola Perusahaan - Wahyuningsih, Sri; Mukti, Aloysius Harry (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
The purpose of this study is to determine the effect of earnings management on firm value and the effect of corporate governance disclosure as a moderating variable in the relationship between earnings management and firm value. Information and data in this study include secondary data. Secondary data is obtained from the company's annual report that has been published. The approach used in this research is a quantitative approach. The sampling method in this study is purposive sampling, namely sampling using certain criteria and obtained as many as 75 data samples. The analytical method used is simple regression analysis and moderated regression analysis with residual test. The test results prove that earnings management has a positive and significant effect on firm value, but the disclosure of corporate governance as a moderation is not able to moderate the relationship between earnings management and firm value. The results of this study can be information for the public, especially for investors to be more careful in assessing companies that have good corporate values.